Pemberdayaan Perempuan Melalui Kewirausahaan dalam Budidaya Ikan Guna Menanggulangi Kemiskinan dan Stunting di Desa Mbatakapidu - Yuniarti Reny Renggo; Meiyasa, Firat; Fitria Dwi Febrianti; Krispina Odilia Wonga; Maria Sisilia Serlin; Kelvin Daniel Tamu Ama; Jeklin Ncini Pau; Lukas Tua Kaber Tena; Lady Grace (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2025)
Poverty and stunting are issues that require attention in a region, necessitating various measures. This is also observed in East Sumba Regency, particularly in Mbatakapidu Village, which has experienced an increase in stunting. Women have an important role in overcoming the problem of stunting. Therefore, women's empowerment needs to be addressed, especially in the field of entrepreneurship through fish farming. The approach taken in this community service activity is a combination of needs-based, asset-based, and service-learning approaches. Abundant water resources present an opportunity for the community to cultivate fish. The results of fish farming are processed into fish floss and fish crackers, which add value and can increase income. Additionally, the nutritional value of fish farming also helps reduce stunting. The results of the Socialization and training activities provided are an increase in understanding and product processing skills for women in Mbatakapidu Village.